Quality Evaluation of The SITASI Final Project System using Selected McCall Software Quality Factors - Adillah, Suci Nur; Ahsyar, Tengku Khairil; Syaifullah, Syaifullah; Anofrizen, Anofrizen; Marsal, Arif (Jurnal Pendidikan Informatika (EDUMATIC), 2025)
The Final Project Information System (SITASI) was developed to support academic administration processes. However, performance and usability issues continue to hinder its effectiveness, particularly during peak usage. This study aims to evaluate the quality of SITASI using the McCall Software Quality Model by focusing on five relevant operational factors: correctness, reliability, efficiency, integrity, and usability. The research employed a descriptive quantitative approach by distributing a validated user perception questionnaire to 72 students with active experience using SITASI. The instrument was tested for validity and reliability, with data analyzed using descriptive statistical techniques to evaluate the quality of the SITASI system. The results show that usability scored the highest at 86%, followed by correctness at 67.6%, reliability at 64.2%, integrity at 50.8%, and efficiency at 43.5%. These findings reveal strong user interface performance but expose technical limitations in speed and data security. The study concludes that while SITASI performs well in terms of usability, it requires substantial improvements in system responsiveness and integrity features. The results offer a structured evaluation of software quality and provide practical recommendations for developers to optimize performance and strengthen data protection. This study contributes a replicable framework for evaluating academic information systems in higher education environments.